Relationship Among Corneal Stiffness, Thickness, and Biomechanical Parameters Measured by Corvis ST, Pentacam and ORA in Keratoconus - Zhao, Yu; Shen, Yang; Yan, Zhipeng; Tian, Mi; Zhao, Jing; Zhou, Xingtao (Frontiers in Physiology, 2019)
PURPOSE: To assess the relationship among corneal stiffness, thickness, and biomechanical parameters in keratoconus. SETTING: The EENT Hospital of Fudan University, Shanghai, China DESIGN: Comparative study METHODS: In this cross-sectional prospective study, 75 keratoconic eyes of 44 patients were recruited. Eyes were divided three groups according to the steepest K-readings (Kmax): mild (31 eyes; 42.1D to 54.5D); moderate (27 eyes, 55.0D to 61.6D); and severe (17 eyes, 65.2D to 94.5D). Thirty-one healthy subjects were recruited as the control group. All patients underwent Corvis ST, Pentacam and ORA examinations at the same time. Stiffness parameter A1 (SP-A1) and other dynamic parameters were assessed using the Corvis ST. Kmax and thinnest corneal thickness (TCT) was obtained using the Pentacam. Corneal resistance factor (CRF) were measured using the ORA. Analysis of correlation was applied to investigate the association between variables. RESULTS: There was a decrease in SP-A1 in different stages of keratoconus compared with controls (P≤0.001): with increasing severity, the value of SP-A1 became smaller (P<0.05). A statistically significant linear relationship was noted between SP-A1 and TCT in each subgroup of keratoconus (P≤0.001). In all three groups, SP-A1 was found to be positively correlated with first applanation time (P<0.01), while negatively correlated with deformation amplitude (P<0.05). Analysis of SP-A1 with regard to CRF and CH indicated statistically positive correlation in keratoconus (P<0.05). CONCLUSION: Significant decreases in corneal stiffness were noted in kerotoconic eyes compared with normal eyes. The stiffness parameter could be a valuable clinical tool enables biomechanically track progression with keratoconus.